Paternal Involvement in and Sociodemographic Correlates of Infant and Young Child Feeding in a District in Coastal South India: A Cross-Sectional Study - Mithra, Prasanna; Unnikrishnan, Bhaskaran; T, Rekha; Kumar, Nithin; Holla, Ramesh; Rathi, Priya (Frontiers in Public Health, 2021)
Context: The feeding practices during first 2 years of life determine the overall health and survival during childhood and beyond. Child nutrition is responsibility of both parents and so far emphasis has been laid mostly on mothers. Fathers' involvement toward Infant and Young child feeding (IYCF) has been proved to be of paramount importance and yet it is given limited importance. Objectives: This study aims to study the level of paternal involvement toward IYCF and its associated factors and to assess the knowledge, attitude, and practices toward IYCF in Dakshina Kannada District in South Indian State of Karnataka. Settings and Design: This community-based cross-sectional study was conducted in the coastal District of Dakshina Kannada; Karnataka State in India. Methods: The study included 450 fathers of infant and young children (aged <2 years) in five taluks of Dakshina Kannada district. They were assessed for knowledge, attitude, and practices related to IYCF. Median score for the practice component was considered cut off to classify involvement in IYCF. Data were analyzed using IBM SPSS Statistics for Windows, Version 25.0. Armonk, NY: IBM Corp. Chi-square-test and Binary Logistic Regression with Hosmer-Lemeshow goodness-of-fit model were used. Unadjusted and adjusted odds ratios were generated. A p-value of <0.05 was considered statistically significant. Results: Mean age of the study population was 34.6 years (SD, 5.4). The practice scores median (IQR) was 34.0 (IQR, 31.0–39.0), and 40.9% of the participants had poor involvement in IYCF. This was significantly higher among fathers from predominantly urban area. Those who had education above graduation and younger fathers had better involvement in IYCF. Conclusions: Less than half of fathers had poor involvement in IYCF, and it was lower among fathers from urban areas, higher age, and lower educational levels.